(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates the intricate relationship between language utilization and the process of negotiating cultural identity among individuals who are learning English as a Foreign Language (EFL) in the region of South Sulawesi, Indonesia. This study examines the various factors that influence the language choices made by learners, as well as the strategies they employ, within their specific sociocultural environment. The research findings demonstrate the crucial significance of the educational setting, the transformative effect of English-language media and global popular culture, and the noteworthy influence of peer groups. The family and home environment play a significant role as cultural foundations, while socioeconomic factors, emotional ties to culture, and regional variations add complexity to the intricate process of negotiating one’s identity. These observations provide a sophisticated comprehension of how English as a Foreign Language (EFL) learners manage their cultural identities via language utilization, underscoring the significance of contextually appropriate and all-encompassing language education methodologies. The research makes a valuable contribution to the wider field of language education and cultural studies by shedding light on the specific dynamics observed in South Sulawesi. It also promotes a more comprehensive viewpoint on the interconnections between language, culture, and identity in English as a Foreign Language (EFL) settings.